Molecular aspects of the antagonistic interaction of smoke-derived butenolides on the germination process of Grand Rapids lettuce (Lactuca sativa) achenes - Soós, Vilmos (The New phytologist, 2012)
© 2012 The Authors. New Phytologist © 2012 New Phytologist Trust.